2017
DOI: 10.1002/ijc.31034
|View full text |Cite
|
Sign up to set email alerts
|

Breast conserving therapy and mastectomy revisited: Breast cancer‐specific survival and the influence of prognostic factors in 129,692 patients

Abstract: This large population-based study compared breast-conserving surgery with radiation therapy (BCT) with mastectomy on (long-term) breast cancer-specific (BCSS) and overall survival (OS), and investigated the influence of several prognostic factors. Patients with primary T1-2N0-2M0 breast cancer, diagnosed between 1999 and 2012, were selected from the Netherlands Cancer Registry. We investigated the 1999-2005 (long-term outcome) and the 2006-2012 cohort (contemporary adjuvant systemic therapy). Cause of death wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
81
2
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(92 citation statements)
references
References 25 publications
6
81
2
3
Order By: Relevance
“…TM may provide women with a safe alternative to mastectomy or offer improved cosmetic and quality‐of‐life outcomes compared with standard BCS, but high‐quality evidence to support the safety and effectiveness of the technique is lacking. RCTs comparing TM with other techniques are largely inappropriate due to patient and surgeon preference, as well as mounting evidence suggesting long‐term survival benefits for patients undergoing BCS and radiotherapy compared with mastectomy. This large prospective multicentre cohort study assessed current practice and short‐term outcomes of the technique and provided ‘real world’ data from 50 centres regarding complications, rates and management of incomplete excision, and impact of TM procedures on the delivery of adjuvant therapy.…”
Section: Discussionmentioning
confidence: 99%
“…TM may provide women with a safe alternative to mastectomy or offer improved cosmetic and quality‐of‐life outcomes compared with standard BCS, but high‐quality evidence to support the safety and effectiveness of the technique is lacking. RCTs comparing TM with other techniques are largely inappropriate due to patient and surgeon preference, as well as mounting evidence suggesting long‐term survival benefits for patients undergoing BCS and radiotherapy compared with mastectomy. This large prospective multicentre cohort study assessed current practice and short‐term outcomes of the technique and provided ‘real world’ data from 50 centres regarding complications, rates and management of incomplete excision, and impact of TM procedures on the delivery of adjuvant therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple randomized studies have demonstrated that breastconserving therapy (partial mastectomy plus whole breast radiation) can yield survival outcomes equivalent to those of mastectomy (1). However, newer population-based data suggest that breast cancerespecific survival and overall survival with breast-conserving therapy may actually be better than those with mastectomy (2)(3)(4)(5)(6)(7)(8). How is this possible?…”
mentioning
confidence: 99%
“…We suggest that adjuvant RT may have a more important role when surgical practice evolves to reduce the volume of tissue resected during breast and axillary surgery. The integral role of adjuvant RT in breast-conserving therapy may explain why it is associated with better breast cancerespecific survival and overall survival relative to mastectomy in several recent population-based studies (2)(3)(4)(5)(6)(7)(8). This improvement in survival is strongest in earlystage subgroups (in which postmastectomy RT is seldom used) and in those with comorbiditiesdfor whom systemic chemotherapy is less often applied (2, 4, 8)dsuggesting possible multimodality interactions.…”
mentioning
confidence: 99%
“…In early-stage breast cancer, high survival rates are achieved irrespective of type of surgery, whether breast-conserving therapy (BCT; breastconserving surgery with breast radiation therapy) or mastectomy (with or without reconstruction). [4][5][6] Consequently, anticipation of outcomes reflecting physical, sexual, and psychosocial functioning is very important in treatment decision-making in these patients.…”
mentioning
confidence: 99%